1980
DOI: 10.1093/jn/110.3.532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manipulating Dietary Protein and Energy Intake on Energy Balance and Thermogenesis in the Pig

Abstract: Weight maintenance was achieved by feeding either restricted amounts of a high-protein diet (HP) or ad libitum amounts of low-protein diet (LP) to 6 and 20 kp pigs for up to 42 days. In all cases, LP animals consumed approximately three times as much energy as the HP animals but in the 20-kp pigs, almost all (70%) of this excess was deposited in the carcass as fat. In 6-kg pigs fed the LP diet, changes in body energy content accounted for only a small fraction (27%) of the total energy intake; a large differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 11 publications
5
34
1
Order By: Relevance
“…The present results indicate changes in the same manner when feeding SPI-with the lower biological value in comparison to CAS+ in all periods at both protein levels. The excess of dietary energy, which cannot be deposited as protein, can either be used for fat deposition (KEAGY et al, 1987) or dissipated as heat GURR et al, 1980). In the present study the total efficiency of utilization of ME (energy retention/ME intake) within periods at both protein levels was not significantly different between CAS+ and SPI-.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The present results indicate changes in the same manner when feeding SPI-with the lower biological value in comparison to CAS+ in all periods at both protein levels. The excess of dietary energy, which cannot be deposited as protein, can either be used for fat deposition (KEAGY et al, 1987) or dissipated as heat GURR et al, 1980). In the present study the total efficiency of utilization of ME (energy retention/ME intake) within periods at both protein levels was not significantly different between CAS+ and SPI-.…”
Section: Discussioncontrasting
confidence: 46%
“…Furthermore, the question arises of how an excess of dietary energy can increase either fat deposition or heat production. GURR et al (1980) demonstrated both metabolic pathways in growing pigs. There were, however, essential differences to our trials.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…According to the authors, the 'missing' energy implied a thermogenic process that was triggered by diet, perhaps in a manner similar to that observed in pigs fed a low-protein diet. 13 These investigators went on to show that cafeteria-fed rats had larger brown fat depots and were significantly more responsive to the thermogenic effects of NE injection. As BAT is the dominant site of energy expenditure in cold-adapted rats, and sympathetic activity is the main driver of cold-induced BAT expansion, the clear inference was that BAT is a major site of diet-induced thermogenesis.…”
Section: The Central Role Of Bat In Nonshivering Thermogenesis and Tmentioning
confidence: 99%